"تعیینِ اہل بیتؓ: اہل سنت والجماعت اور اہل تشیع کے نقطہ نظر کا تحقیقی و تقابلی جائزہ": THE IDENTIFICATION OF AHL AL-BAYT: AN ANALYTICAL AND COMPARATIVE STUDY OF THE PERSPECTIVES OF AHL AL-SUNNAH WA’L-JAMĀ’AH AND THE SHĪ’ AH" (Al-Aasar, 2025)
The concept of Ahl al-Bayt (People of the House) holds significant theological and historical importance in Islamic thought. However, Muslim sects differ regarding the exact identification of who constitutes the Ahl al-Bayt. This study seeks to conduct a critical and comparative analysis of the views of Ahl al-Sunnah wa’l-Jamā‘ah and Shi‘ah regarding the identification (taʿyīn) of Ahl al-Bayt. The research investigates primary sources including Hadith collections, exegetical texts, and statements of classical scholars to explore the scope and members defined as Ahl al-Bayt by each school of thought. The study highlights three primary approaches: identification based on lineage (nasab), residence (sukūn), and birthplace (wilādah) in the Prophet’s household. It reveals that while both sects hold deep reverence for the Ahl al-Bayt, they differ in their criteria of inclusion. This scholarly comparison helps clarify theological distinctions and promotes a deeper understanding of intra-Muslim perspectives.